Representamos a la decena como unidad - Mauricio Vargas, Gladys Marilu (2019)
The present lesson plan of the Mathematics area entitled “We represent the ten as a unit” is designed for the Second Grade of Primary Education, taking into account the approach focused on Problem Solving. It is also oriented to class planning with their respective moments, strategies, abilities, performance to be achieved and the evidence of learning that each student must achieve at the end of the class. In Theoretical Support, the conceptual definitions of the main variables of the subject to be treated are exposed, with the purpose of explaining the above with a base that supports it. Similarly, the Pedagogical Support will address the foundation of the Mathematics Area, the approach that underpins it, the pedagogical and didactic processes of the area, as well as the evaluation techniques and instruments according to the new Curriculum Framework, considering the profile of Exit that the student must have at the end of Regular Basic Education.